NMOS DEVICE OPTIMIZATION AND FABRICATION USING ATHENA & ATLAS SIMULATION SOFTWARE - CHOW , KIM POH (Universiti Teknologi Petronas, 2004)
Experiment has proven that NMOS performs better than PMOS due to higher drive current, higher mobility, easier to implement scaling technology and low power consumption. However, there is still room for further optimization as the technology trend for the miniaturization ofNMOS and integrated devices continue to grow. In this project, several objectives have been outlined to be completed within 2 semester period. These include detailed understanding of fabrication aspect and NMOS properties, optimizing NMOS by reducing threshold voltage, minimizing off-stage leakage, reducing gate length, increasing switching speed and designing a mixed mode circuit. However, the cost required to perform experimental analysis and optimization of semiconductor devices using fabrication process can be very expensive especially when involving purchase of expensive electrical testing equipment. Thus, it is recommended to perform optimization and analysis using simulation. One ofthe best device process and simulation tool is Silvaco ATHENA & ATLAS simulation software. It provides user with various capability in process and electrical testing. After manipulating and improving process parameters, the optimized device has recorded significant improvement over the predecessor. Optimizations include better threshold voltage extraction (0.2v), drain current rise beyond pinch off, better drain current extraction, higher switching speed at 2Ghz, better device structure after ion implantation due to tilted implantation, lower off-stage leakage current (1.2589 x 10' A/um) and minimization ofjunction breakdown effect.